2001
DOI: 10.1046/j.1439-0442.2001.00393.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nigella sativa on Glucose Concentration, Lipid Peroxidation, Anti‐Oxidant Defence System and Liver Damage in Experimentally‐Induced Diabetic Rabbits

Abstract: This study was carried out to investigate whether Nigella sativa could decrease the lipid peroxidation, increase the anti-oxidant defence system and also prevent the lipid-peroxidation-induced liver damage in experimentally induced diabetic rabbits. Fifteen New Zealand male rabbits were divided into three experimental groups: control, diabetic and diabetic and N. sativa-treated. The diabetes mellitus (DMI) was induced in the rabbits using 150 mg/kg of 10% alloxan. The diabetic + N. sativa-treated group was giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
107
1
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(126 citation statements)
references
References 20 publications
15
107
1
3
Order By: Relevance
“…Recently, many therapeutic effects of NS extracts have been documented, including antioxidant (Burits and Bucar, 2000;Balikci, 2010), antimicrobial, antihelmintic (Agarwal et al, 1979), anti-inflammatory (Houghton et al, 1995), anti-tumour (Worthen et al, 1998), anti-diabetic (Meral et al, 2001) and antiulcerogenic (Akhtar et al, 1996) effects in both clinical and experimental studies. With this study we aimed at comparatively analyzing the effects of NS and SSD on wound healing in a burn wound model.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many therapeutic effects of NS extracts have been documented, including antioxidant (Burits and Bucar, 2000;Balikci, 2010), antimicrobial, antihelmintic (Agarwal et al, 1979), anti-inflammatory (Houghton et al, 1995), anti-tumour (Worthen et al, 1998), anti-diabetic (Meral et al, 2001) and antiulcerogenic (Akhtar et al, 1996) effects in both clinical and experimental studies. With this study we aimed at comparatively analyzing the effects of NS and SSD on wound healing in a burn wound model.…”
Section: Discussionmentioning
confidence: 99%
“…Meral et al induced diabetes in rabbits using 150 mg/ kg of 10% alloxan. Oral N. sativa treatment for 2 months in these rabbits, decreased the elevated glucose and malondialdehyde (MDA) concentrations, increased the lowered glutathione (GSH) and ceruloplasmin concentrations, and prevented lipid-peroxidation-induced liver damage in diabetic rabbits [59]. Anti-diabetic action of N. sativa is at least partly mediated through decreased liver gluconeogenesis [60].…”
Section: Possible Mechanisms Of Antidiabetic Activitymentioning
confidence: 99%
“…Thymoquinone, the major component of the essential oil, is the biologically active gradient of this plant (Ali and Blunden, 2003) . It was reported that, thymoquinone(TQ) has many medicinal properties like; anti-oxidant (Meral et al, 2001;Shalaby and khater, 2007;Zegarac et al, 2009 ), anti-inflammatory (Hajhashemi et al, 2004), anti-tumor (Banerjee et al, 2010), analgesic and other properties (Kaleem et al, 2006;Bhatti et al, 2009). On the other side, Kapoor ( 2009) proved that TQ protects hepatic tissue from deleterious effects of toxic metals such as lead, and attenuates hepatic lipid peroxidation following exposure to chemicals such as carbon tetrachloride.…”
Section: Introductionmentioning
confidence: 99%